Exploring the role of website attributes in satisfaction and online impulse buying behavior - MOUMEN , Houda; ABAAOUKIDE , Kamar (Revue Internationale des Sciences de Gestion, 2025)
Online impulse buying behavior “OIBB” is a major area of study in consumer behavior due to the exponential growth of e-commerce. Although previous research has mostly concentrated on quantitative analyses, little is known about the experiential aspect of consumers’ impulsive online purchases. Using 21 semi-structured interviews with Moroccan consumers who have engaged in OIBB. The study examines the effects of both utilitarian and hedonic website attributes on user satisfaction and OIBB, with a foundation in the Stimulus–Organism–Response (S-O-R) model. Results show that emotional engagement, perceived trust and OIBB are influenced by features like payment options, return policies, navigation features, and product recommendations. When supported by website attributes, satisfaction turns into a mediator that reinforces OIBB. On the other hand, dissatisfaction acts as a barrier to impulsivity. The findings offer theoretical and managerial repercussions since they provide a better understanding of the processes behind online impulse buying behavior. They also recommend that increasing website design and efficiency can be influential for user satisfaction and unplanned purchasing decisions.